2023
DOI: 10.3390/microorganisms11081945
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nanoparticle Uptake by Myzocytosis and Endocytosis in Colpodella sp. ATCC 50594

Tobili Y. Sam-Yellowe,
Mary M. Asraf,
John W. Peterson
et al.

Abstract: Colpodella sp. (ATCC 50594) is a free-living biflagellate predator closely related to pathogenic Apicomplexa such as Plasmodium, Cryptosporidium and Toxoplasma gondii. Colpodella sp. (ATCC 50594) obtain nutrients by preying on Parabodo caudatus using myzocytosis. The organization of the myzocytic apparatus and the mechanism of nutrient uptake into the posterior food vacuole of Colpodella species is unknown. In this study, we investigated myzocytosis using light and transmission electron microscopy. We investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In previous studies we showed that the process of myzocytosis in Colpodella sp. (ATCC 50594) occurs sequentially, beginning with attachment to the prey P. caudatus, engulfment of the plasma membrane of the prey, destruction of the prey's plasma membrane and aspiration of the prey's cytoplasmic contents into a posterior food vacuole [25]. In addition to myzocytosis for nutrient uptake, Colpodella sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies we showed that the process of myzocytosis in Colpodella sp. (ATCC 50594) occurs sequentially, beginning with attachment to the prey P. caudatus, engulfment of the plasma membrane of the prey, destruction of the prey's plasma membrane and aspiration of the prey's cytoplasmic contents into a posterior food vacuole [25]. In addition to myzocytosis for nutrient uptake, Colpodella sp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to myzocytosis for nutrient uptake, Colpodella sp. (ATCC 50594) trophozoites can also carry out endocytosis in culture [25]. Following myzocytosis, and nutrient acquisition, Colpodella sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…before the degradation of the membrane. This aperture may represent a structure similar to the cytostome [ 13 ]. Once inside the predator’s cytoplasm, the prey’s cytoplasmic contents are aspirated across a tubular tether into the posterior food vacuole of the predator [ 13 ].…”
mentioning
confidence: 99%
“…This aperture may represent a structure similar to the cytostome [ 13 ]. Once inside the predator’s cytoplasm, the prey’s cytoplasmic contents are aspirated across a tubular tether into the posterior food vacuole of the predator [ 13 ]. The resemblance of the myzocytic aperture to the cytostome remains speculative and will require experimental studies for verification.…”
mentioning
confidence: 99%